2012
DOI: 10.1159/000341690
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin, NF-ĸB, and Cancer: The Dark Side of Cytokines

Abstract: Cytokines have been implicated in a variety of physiological processes involving lymphoid tissue development, lymphocyte activation, and control of regenerative processes such as wound healing. The first characterization of a cytokine implicated in abolishing or killing tumor cells – the tumor necrosis factor (TNF) – fostered and boosted a completely new field of research that in addition to cancer research started to generate an overwhelming amount of knowledge in immunology, various pathological processes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 223 publications
1
50
0
Order By: Relevance
“…Many immune regulatory cytokines are produced in the lymph nodes, which nurture and modulate immune cell proliferation, maturation, migration, and defense functions. Among these, Lymphotoxin‐β (LTβ) is one of the crucial cytokines produced by lymphocytes and lymphoid tissues . LTβ is an anchored transmembrane protein of 244 aa (18.5 KDa), that can form soluble heterotrimers (LTα1β2, or LTα2β1), which are shed from the cell surface by proteolytic cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Many immune regulatory cytokines are produced in the lymph nodes, which nurture and modulate immune cell proliferation, maturation, migration, and defense functions. Among these, Lymphotoxin‐β (LTβ) is one of the crucial cytokines produced by lymphocytes and lymphoid tissues . LTβ is an anchored transmembrane protein of 244 aa (18.5 KDa), that can form soluble heterotrimers (LTα1β2, or LTα2β1), which are shed from the cell surface by proteolytic cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…The proteins of the LTA , LTB, and TNFA genes are involved in several pathophysiological processes, especially in the complex network of the local inflammatory cascade, inducing vasodilation and depletion of leukocyte cells. However, a change on their expression may generate an unfavorable and hazardous environment to the organism …”
Section: Discussionmentioning
confidence: 99%
“…4,11,[13][14][15]41,50 To the author's knowledge, there is no study with LTA, TNFA, and LTB genes and to the organism. 17,51,52 Polymorphisms in those genes are responsible for the modulation of numerous diseases. 27 Polymorphisms in the LTA gene have already been associated with distinct pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…[86][87][88] NF-κB can accelerate the adhesion of tumor cells to epithelial cells and matrix, induce tumor cells to generate protease so as to degrade extracellular matrix, and promote vascularization. [89,90] Sliva et al, found that lucid ganoderma exerted the inhibiting effects on the migration of high invasive non-estrogen receptor-dependent breast cancer cell via inhibiting NF-κB signal pathway.…”
Section: Influence Of Traditional Chinese Medicines and The Active Inmentioning
confidence: 99%